The Needs for Improvements of Value Chain in Livestock Smallholder Farmers in Indonesia - Guntoro, Budi (Malaysian Society of Animal Production, 2014)
Value chain approaches play an important role in characterizing the complex networks, relationships, and intensives that exist in livestock systems. They further provide framework for mobilizing pro-poor development in the context of agri-food networks that facture livestock across a range of livelihood-improving roles for the rural poor. This paper will discuss about the needs for improvements of value chain in livestock smallholder farmer in Indonesia. It ranges starting from how value chain framework in animal products, such as value chain constraints, value chain government, value added, and upgrading option, to how may participatory approach help to fulfill the need, such as farmer's involvement in the chain, and identification of farmer's needs. Finally, paper recommends the development Intervention strategies.